2016
DOI: 10.3855/jidc.6569
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon and Chinese herbs exert a combinatorial effect in HBeAg-positive chronic hepatitis B

Abstract: Introduction: Traditional Chinese herbs are widely used for the treatment of chronic hepatitis B (CHB) in China. The aim of this study was to perform a meta-analysis of randomized controlled trials (RCTs) comparing peginterferon therapies with peginterferon plus Chinese herbal therapies in hepatitis B e antigen (HBeAg)-positive CHB patients. Methodology: The main biomedical databases were searched to identify RCTs that compared the efficiency of peginterferon with peginterferon plus Chinese herbs in CHB patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Beginning around 1950, scientific evaluation of herb materials used for treatment of viral hepatitis was accepted in China and Japan. Current studies from Gao et al showed that the combination therapy with peginterferon plus Chinese herbs exerted combinatorial effects in HBeAg(+) CHB patients [15]. Our previous studies showed that BSF had beneficial effects on CHB patients with mildly elevated ALT (1–2 times ULN) by reducing serum ALT and HBV DNA levels, which was relevant with the decrease of CD4 + CD25 + T cell frequency and the increase of the IFN- γ level in CD4 + T cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Beginning around 1950, scientific evaluation of herb materials used for treatment of viral hepatitis was accepted in China and Japan. Current studies from Gao et al showed that the combination therapy with peginterferon plus Chinese herbs exerted combinatorial effects in HBeAg(+) CHB patients [15]. Our previous studies showed that BSF had beneficial effects on CHB patients with mildly elevated ALT (1–2 times ULN) by reducing serum ALT and HBV DNA levels, which was relevant with the decrease of CD4 + CD25 + T cell frequency and the increase of the IFN- γ level in CD4 + T cells [16].…”
Section: Introductionmentioning
confidence: 99%